Risk factors for positive tuberculin tests in children - Purnomo Sidhi; Dwi Wastoro Dadiyanto; Suhartono Suhartono (Paediatrica Indonesiana, 2011)
Background Tuberculosis (TB) is a chronic infectious disease and a public health problem. The World Health Organization (WHO) declared TB to be a global emergency because of currently increasing rates of disease and drug resistance. Two million people die annually because of TB. Children are one of the highest groups at risk for TB infection. An effort to define risk factors is needed for effective intervention.Objective To identify risk factors for positive tuberculin tests in children.Methods This case control study was done in elementary school children aged 8–12 years in areas served by three community health centers in Semarang. Twenty-nine subjects were Mantoux positive and 29 others served as controls. Consecutive sampling was used for all negative Mantoux test results. Pulmonary TB was diagnosed using the TB scoring system, including the Mantoux test. Statistical bivariate and multivariate analyses were performed.Results History of household TB contact as a risk factor for positive tuberculin test in children resulted in an OROR of 3.76 (95% CI 1.059 to 13.342), P=0.040. History of illness at the time of testing resulted in an OR of 10.23 (95% CI 1.138 to 91.930), P=0.038. The probability of positive tuberculin testing was 90.7% if both these variables were positive.Conclusion History of household TB contact and the history of illness at the time of testing were risk factors for positive tuberculin tests in children.